A caffeic acid phenethyl ester analog inhibits the proliferation of nasopharyngeal carcinoma cells via targeting epidermal growth factor receptor. Issue 7 (3rd March 2020) - Ning, Xianhui; Ren, Xiabin; Xie, Xiaofeng; Yan, Ping; Wang, Dehui; Huang, Xinsheng
Abstract: A previous study reported that compound 5A, a caffeic acid phenethyl ester (CAPE) analog, exhibited obvious neuroprotective activity, in particular, compound 5A possessed higher stability and membrane permeability than CAPE. CAPE displays antitumour function; therefore, evaluating the antitumour effect of its analog with higher stability and membrane permeability is worthwhile. We first investigated the antitumour activity of compound 5A. We found that compound 5A significantly inhibited the proliferation of tumor cells and showed low cytotoxicity in normal cells. Furthermore, compound 5A was found to induce the cell cycle arrest and apoptosis of CNE2 cells. Through the prediction of SwissTargetPrediction and subsequent confirmation, epidermal growth factor receptor (EGFR) was identified as a target of compound 5A. Compound 5A also influenced the expression of genes downstream of EGFR in nasopharyngeal carcinoma (NPC) cells. Based on these findings, compound 5A inhibits the proliferation of NPC cells by targeting EGFR and may become a new candidate compound for NPC treatment.